KOMPOSISI DAN STRUKTUR POHON RIPARIAN DI SUNGAI KAHALA KABUPATEN KUTAI KARTANEGARA - Muhammad Basrowi; Medi Hendra; Nova Hariani (Jurnal Pro-Life, 2018)
The aim of this study is to assess the design of physiognomy of riparian trees and the composition and vegetation structure of riparian trees formation in some forest types in Kahala river of Kutai Kartanegara district, East Kalimantan. The method used in this study was the vegetation ecology which the quadrant technique was applied to collect main primary data of the riparian trees. Points of data retrieval were carried out by as much as 3-point observations at the upper, middle and lower of Kahala river basin. The location of each point was marked by GPS with the length of each transect was 1 km away. The parameters of plant composition and structure ware analyzed by measuring density (K-i), frequency (F) and (dominance). The result showed that physiognomy of riparian trees in 3 main locations was mature secondary forest (in the upstream), perupuk forest (the midstream) and early immature secondary forest (the downstream). There were 22 species belonging to 16 families of riparian trees were recorded in Kahala river. The plant species that have high the importance value (I.V) were recoded namely Antidesma ghaemsembilla which 122.8 % (in the downstream) and Lophopetalum javanicum which 58.5 % (in the upstream).Keywords: Kahala River, Riparian Trees and Quadrant Method.